POLA KOMUNIKASI ORANG TUA DENGAN ANAK AUTIS (Studi pada orang tua dari anak autis di Sekolah Luar Biasa AGCA Center Pumorow Kelurahan Banjer Manado) - Boham, Sicillya E. (ACTA DIURNA KOMUNIKASI, 2013)
The autism disorder of children is a disease of socialisation aspect so that children are difficult to behave especially to communicate or interact together with other peoples in their envoriontment. The mode of parental communication with the children is trhough the obedience training on and through eye contact, and by reward and punishment. Any other action such as embarcing, erasing and etc.